P4_1 The 'Fatman' - Jupp, Matt; Yeomans, Kieran; Cobley, Dillon; Fenlon-Smith, Domonic (Physics Special Topics, 2016)
In this paper we investigated the feasibility of the M42 `Fat Man' by considering the recoil felt on a person when firing the $5.5$ kg projectile. It was found that a muzzle velocity of $v = 32.1$ms$^{-1}$ is required to fire the projectile $105$ m when air resistance was taken into account. To achieve this muzzle velocity a pressure of $P = 16.1$x$10^6$ Pa is required in the pneumatic firing system. It was found that the recoil of the system is $p = 188.1$ kgms$^{-1}$. The M42 `Fat Man' was determined to be a feasible weapon system.